ANALYSIS OF FINANCIAL STATEMENTS OF MSMES AT THE IMPLEMENTATION OF FINANCIAL ACCOUNTING STANDARDS OF SMALL AND MEDIUM ENTITY (SAK EMKM) - Utari, Indah Hari; Subandoro, Agus; Sari, Anita Kartika; Yulfajar, Amrina; Harjanti, Wulandari (Universitas 17 Agustus 1945 Surabaya, 2022)
This study aims to encourage SMEs that do not yet have a record of financial statements to apply their financial statements in accordance with the Accounting Standards for Micro, Small and Medium Entities, in presenting simple reports with an accounting financial report preparation system that can help and simplify. The study was conducted on the MSME business of Nasi Pecel Food Stall Madiun Dika Bolo. The method used is descriptive qualitative method. As well as collecting data by means of interviews, documentation and direct observation. This study was conducted to analyze the preparation of financial statements in accordance with the statement of SAK EMKM. It is known that Warung Nasi Pecel Madiun Dika Bolo has problems in preparing financial statements, including the lack of manpower and bookkeeping to make financial reports, only recording income and expenses in order to find the profit side due to lack of knowledge related to how to make financial reports so that according to SAK EMKM.